SG-APSIC1101: Virulence factors and antimicrobial resistance in coagulase-negative staphylococci isolated from blood of neonates - Svetlana Kolesnichenko; Irina Kadyrova; Alyona Lavrinenko; Lyudmila Akhmaltdinova; Lyudmila Panibratec (Cambridge University Press, 2023)
Objectives: To determine virulence genes and sensitivity to antibacterial drugs of Staphylococcus epidermidis isolated from blood cultures of newborns. Methods: A study of сoagulase-negative Staphylococcus (CoNS) from newborns with sepsis was conducted in the regional perinatal center in Karaganda, Kazakhstan. Blood-culture identification was performed using MALDI-TOF MS. Virulence factors were determined on primers (sdrG, sdrG, atl, lip, nuc, ebh, hlb, sspA, sspB, and gehD) with PCR (Bio-Rad CFX 96). Susceptibility to antibiotics determination was carried out using the disc-diffusion method. Testing with cefoxitin was used to detect methicillin resistance in staphylococci. Results: Overall, 18 Staphylococcus epidermidis isolates from blood cultures of newborns with sepsis were investigated from January to December 2021. The frequency of detection of virulence genes was distributed as follows: atl (94.5%), sspB (94.5%), sspA (89%), gehD (89%), ebh (89%), hlb (72%), sdrG (39%), sdrF (28%), nuc (28%), and lip (13%). Also, 10 isolates (55%) were resistant to cefoxitin (MRSE). Furthermore, 72% of S. epidermidis isolates showed resistance to azithromycin and 33% were resistant to clindamycin and gentamicin. Also, 39% of strains were resistant to fluorchinolones. All isolates were susceptible to vancomycin, linezolid, and fusidic acid. Conclusions: S. epidermidis strains isolated from blood cultures had high rates of exoenzymes sspB, sspA, gehD, autolysin (atl), β-hemolysin (hlb), and cell-wall-associated fibronectin-binding protein (ebh). Among 18 neonatal sepsis pathogens, 10 (55%) were MRSE, so it is necessary to pay attention to antibiotic therapy adjustment.